Occurrence and Distribution of 16 Human Morphogenetic Traits in the Maseru District of Lesotho
Background: Morphogenetic traits are used in human identification in forensic investigations and demonstration of basic genetics but without agreement on inheritance patterns in all cases. Method: The distribution of 16 morphogenetic traits among 505 students were analyzed, performed Chi-squared (χ ^2 χ2) analysis to determine conformity of the traits with the genetic model of one-gene with two-alleles and association between trait and gender; distribution of the traits among 114 offspring of 46, H X H, H X N and N X N parental pairs was analyzed to determine if the traits are monogenic or polygenic and for association between parents and offspring. Results: The dominant phenotype was more prevalent (%) for ear lobe, tongue rolling, tongue folding, bent little finger, index/ring finger, widow’s peak, eyebrow shape and handedness but, less prevalent for dimple, cleft chin, hand clasping, arms folding, white forelock, ear pit, longer 2nd toe and gap tooth. No significant association between gender and any trait, χ2 (1, N = 505) < 3.48, p > .05). χ ^2 χ2 analysis of observed and expected numbers of phenotypes of cheek dimple, cleft chin, hair line, white forelock, ear pit, longer 2nd toe and gap tooth fitted the Hardy-Weinberg assumptions and were considered monogenic traits. Results for 9 traits deviated from the H-W assumptions and were considered polygenic. Analyses of the distribution of the traits among the 114 offspring showed that the heterozygotes (HN) outnumbered the homozygotes (HH or NN) among the dominant phenotypes for 14 traits which suggested that the recessive alleles were protected in the dominant phenotypes. Except for hair line where H X H pair produced only H offspring and white forelock, where N X N pair produced only N offspring, the three different pairs produced both H and N offspring. Association between parents and offspring was observed because, most H x H pairs produced more H than N and most N X N pairs produced more N than H offspring. Conclusion: Production of H offspring by N X N or N offspring by H X H parents suggested that such traits are not monogenic, the parents not homozygotes and/or “paternal discrepancy" and demonstrate the complex inheritance patterns of morphogenetic traits that should be explained when used to demonstrate basic genetics principles. , number=5, journal=British Journal of Healthcare and Medical Research, author=Asita, Asita Okorie and Ntsane, Khahliso and Taole, Matsepo Motselisi, year=2022, month=Nov., pages=403–425